Belatacept in renal transplant recipient with mild immunologic risk factor: A pilot prospective study (BELACOR). Issue 3 (25th January 2019) - Leibler, Claire; Matignon, Marie; Moktefi, Anissa; Samson, Chloé; Zarour, Anissa; Malard, Stéphanie; Boutin, Emmanuelle; Pilon, Caroline; Salomon, Laurent; Natella, Pierre‐André; Durrbach, Antoine; Robert, Thomas; et al.
Abstract : The benefit of belatacept on antibody‐mediated rejection (ABMR) incidence after kidney transplant with preformed donor‐specific antibodies (DSAs) has never been assessed. Between 2014 and 2016, we conducted a multicenter prospective clinical trial with 49 patients to determine kidney allograft outcome in recipients with preformed DSAs (maximal mean fluorescence intensity 500 to 3000) treated with belatacept (BELACOR trial). Immunosuppressive strategy included antithymocyte globulin, belatacept, mycophenolate mofetil, and steroids. An ancillary control group was designed retrospectively, including patients fulfilling the same inclusion criteria treated with calcineurin inhibitors. In BELACOR group, no patient exhibited acute ABMR, patient and allograft survival at 1 year was 100% and 95.4%, respectively, and the estimated glomerular filtration rate was 53.2 mL/min/1.73 m 2 . However, the 12‐month incidence of acute T cell–mediated rejection was 25.4% (14.5% to 42.4%). Comparison with the control group showed significantly higher T cell–mediated rejection incidence only in the BELACOR group ( P  = .003). Considering the DSAs, the outcome was similar in the 2 groups except a significantly higher number of patients displayed a complete disappearance of class II DSAs in the BELACOR group ( P  = .001). Belatacept was not associated with an acute ABMR increased risk and may be considered as immunosuppressive strategy in transplant recipients with preformed DSAs (maximal mean fluorescence intensity 500 to 3000). Prospective randomized trials are needed to confirm these results. Abstract : The BELACOR prospective clinical trial finds no increased risk of antibody‐mediated rejection when kidney transplant recipients with mild immunological risks are treated with belatacept.